Venezuela in the Caribbean : expanding its sphere of influence - Sanders, Ronald (2007)
Analyzes the traditional relationship between Caricom and the USA, on the one hand, and the new relationship with Venezuela, on the other, and argues that the Caricom countries, small though they are, will act in their own interests.